Effectiveness of a youth-led early childhood care and education programme in rural Pakistan: A cluster-randomised controlled trial - Yousafzai, Aisha K.; Rasheed, Muneera A.; Rizvi, Arjumand; Shaheen, Fariha; Ponguta, Liliana A.; Reyes, Chin R. (PLOS ONE, 2018)
Background The United Nation’s Sustainable Development Goals encompass lifelong learning from birth to youth to adulthood (Goal 4) and economic opportunities for young people (Goal 8). The targets include improving access to quality early childhood care and education (ECCE) as well as learning and training opportunities for adolescents and youth. Cross-generational models for young children and youth may offer opportunities to address the interconnections between goals and targets for the next generation. We investigated whether an ECCE programme for young children (3.5–6.5 years) delivered by female youth (18–24 years) in rural Pakistan would be effective on children’s school readiness. Methods In partnership with the National Commission for Human Development in Pakistan, we implemented the ‘Youth Leaders for Early Childhood Assuring Children are Prepared for School’ (LEAPS) programme to train female youth to deliver ECCE. The effectiveness of the LEAPS programme on children’s school readiness was evaluated in a cluster-randomised controlled trial. We randomly allocated five clusters (villages) to receive the intervention (n = 170 children) and five clusters to control (n = 170 children). Children’s school readiness was assessed after nine months of intervention exposure using the International Development and Early Learning Assessment tool. Analyses was by intention-to-treat. The trial is registered with ClinicalTrials.gov, number NCT02645162. Findings At endline, the intervention group had significantly higher school readiness scores (n = 166, mean percentage score 59.4, 95% CI 52.7 to 66.2) compared with the control group (n = 168, mean percentage score 45.5, 95% CI 38.8 to 52.3). The effect size (Cohen’s d) was 0.3. Conclusion Trained female youth delivered an ECCE programme that was effective in benefitting young children’s school readiness. The cross-generational model is a promising approach to support early child development; however, further evaluation of the model is needed to assess the specific benefits to youth including their skills and economic development.
Keywords: Caregivers; Child development; Children; Human learning; Pakistan; Schools; Supervisors; Teachers

Assessing Early Childhood Fluid Reasoning in Low- and Middle-Income Nations: Validity of the Wechsler Preschool and Primary Scale of Intelligence Across Seven MAL-ED Sites - Ruan-Iu, Linda; Pendergast, Laura L.; Rasheed, Muneera; Tofail, Fahmida; Svensen, Erling; Maphula, Angelina; Roshan, Reeba; Nahar, Baitun; Shrestha, Rita; Williams, Brittney; Schaefer, Barbara A.; Scharf, Rebecca; et al. (Journal of Psychoeducational Assessment, 2019)
An adapted version of the Wechsler Preschool and Primary Scale of Intelligence—Third Edition (WPPSI-III) was administered to assess cognitive functioning among 1,253 5-year-old children from the Malnutrition and Enteric Disease (MAL-ED) study—an international, multisite study investigating multiple aspects of child development. In this study, the factor structure and invariance of the WPPSI-III were examined across seven international research sites located in Bangladesh, Brazil, India, Nepal, Pakistan, South Africa, and Tanzania. Using a multiple indicator multiple cause (MIMIC) modeling approach, the findings supported the validity of a fluid reasoning dimension (comprised of block design, matrix reasoning, and picture completion subscales) across each of the seven sites, although the scores were noninvariant. Accordingly, these scores are recommended for research purposes and understanding relationships between variables but not for mean comparisons or clinical purposes.